2014
DOI: 10.1371/journal.pone.0114603
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting-State Connectivity in College Students with Nonclinical Depressive Symptoms

Abstract: BackgroundThe underlying brain basis of nonclinical depressive symptoms (nCDSs) is largely unknown. Recently, the seed-based functional connectivity (FC) approach for analyzing resting-state fMRI (rs-fMRI) data has been increasingly used to explore the neural basis of depressive disorders. Other than common seed-based FC method using an a priori seed region, we conducted FC analysis based on regions with altered spontaneous activity revealed by the fractional amplitude of low-frequency fluctuations (fALFF) app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…In addition, increased DC in the left IFG (BA 44) was observed in subclinical depressive subjects in the present study. Similarly, the abnormalities of left IFG have been increasingly reported in MDD (Guo et al, 2012) and nonclinical depression (Wei et al, 2014). It was suggested that deficits in semantic labeling of negative emotions were related to increased activation in left IFG in medication-free depressed individuals (van Wingen et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, increased DC in the left IFG (BA 44) was observed in subclinical depressive subjects in the present study. Similarly, the abnormalities of left IFG have been increasingly reported in MDD (Guo et al, 2012) and nonclinical depression (Wei et al, 2014). It was suggested that deficits in semantic labeling of negative emotions were related to increased activation in left IFG in medication-free depressed individuals (van Wingen et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…However, no study so far has investigated DC alterations in subclinical depression. As there have been very few studies focused on subclinical depression in young adults and the brain alterations of subclinical depression are largely unknown (Wei et al, 2014, 2015), the DC approach without requiring a priori selection is a promising strategy to uncover the neural basis of subclinical depression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent RSFC study among college students with nonclinical depressive symptoms found altered connectivity in both the bilateral ITG and IFG [55]. In addition, hyperconnectivity within the DMN and hypoconnectivity within the CCN may distinguish adults with treatment-resistant depression [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…First, the size of the study sample could be an issue. Although it was suitable for fALFF analysis, the sample size in each group was relatively small, which might result in some subtle functional changes in the brain not being observed [51]. In addition, the inclusion criteria for education level in this study might be a possible bias and confounding issue.…”
Section: Limitationsmentioning
confidence: 99%